The Most Bothersome Aspects of Off Periods Reported by Individuals with Parkinson's Disease. Issue 3 (5th March 2020) - Chahine, Lana M.; Edison, Briana; Daeschler, Margaret; Mantri, Sneha; Kahl, Steven; Rapoport, Robyn; Goyle, Arina; Precht, Chelle; Kopil, Catherine; Marras, Connie
ABSTRACT: Introduction: The off periods in Parkinson's disease have a significantly negative impact on quality of life. What the most bothersome aspects of off periods are from the patient's perspective are not well studied, nor is the degree to which screening tools for wearing off such as the Wearing Off Questionnaires (WOQs) capture what bothers patients most. Methods: A questionnaire was deployed to eligible participants of Fox Insight, an online study of individuals with self‐reported Parkinson's disease. Inclusion criteria were the use of ≥1 dopaminergic medications and an affirmative response to a question on experiencing off periods. Participants provided free‐text responses regarding the top 3 most bothersome symptoms they experience when off . A determination was made regarding whether each response would have been captured by the 32‐item, 19‐item, and 9‐item WOQs. Results: The final sample had 2106 participants, a mean age of 66.6 years, 52.3% were men, and had a disease duration of 4.9 years. The WOQ‐32 items covered all of the most bothersome symptoms for 53.2% of respondents. Among bothersome aspects of off not captured by the WOQs, 597 (66.2%) were specific symptoms, with freezing of gait, apathy, and memory problems being the most common. The functional consequences of off periods were most bothersome to 232 (25.7%), with walking problems being the most common. The emotional response to off periods was the most bothersome aspect to 169 respondents (18.7%). Discussion: This study emphasizes the value of narrative data in understanding patient experiences, and what bothers patients most about off periods. The WOQs, although of established utility in the screening for wearing off, may not capture those symptoms most bothersome to patients.